PERBANDINGAN KINERJA KEUANGAN PADA BANK MANDIRI DAN BRI MENGGUNAKAN ANALISISRISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, DAN CAPITAL (RGEC) PERIODE 2019-2023 - Sulastri Eka Pratiwi; Yulian Bayu Ganar (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This study is intended to evaluate the financial performance of Bank Mandiri and Bank BRI during the 2019-2023 periode using the RGEC approach, analysis is conducted through four aspects, Risk Profile, Good Corporate Governance (GCG), Earnings, and Capital. This research employs a descriptive quantitative approach utilizing secondary data obtained from the banks’annual reports. The Results show that overall both banks fall into the healthy category. Bank Mandiri experienced fluctuations in NPL and LDR ratios, while BRI recorder an increase in NPL at the end of the period. In terms of GCG, Bank Mandiri was ranked 1 (very healthy), whereas BRI was ranked 2 (healthy). The earnings performance measured by ROA, NIM, and BOPO, of both banks remained positive despite the impact of the pandemic, and their capital ratios consistently exceeded the industry standards.